Intestinal intussusception as a metastatic presentation of Acral Melanoma – Case report - Martínez Zamorano, Monserrat; Flores Solares, Elizabeth; Prado Salcedo, Tatiana Andrea; Aguilera de Alba, Karen Sofía; Sanchez Martínez, María de Lourdes (Current problems in cancer. Case reports, 2025)
•Acral melanoma occurs on hairless skin, it isn't associated with ultraviolet radiation exposure.•Intussusception is an extraordinarily rare clinical entity in adults and the most common cause is a neoplasm.•Think cancer in an adult intussusception. Acral melanoma is a clinical subtype of melanoma that occurs on surfaces that do not develop hair, frequently metastasizes, and presents significant recurrence. Intestinal metastasis occurs in 0.3 % of cases and may exceptionally manifest as intussusception. A young adult man diagnosed with clinical stage IV acral melanoma came to the emergency room with abdominal pain, nausea, and hematemesis. An abdominal tomography was performed with data of intestinal intussusception with subsequent emergency laparotomy showing ileo-ileal invagination secondary to a hyperpigmented tumor lesion. Acral melanoma rarely develops intestinal metastases and it is even rarer to cause intussusception compared to other types of melanoma. Imaging studies are useful for diagnosis and emergency laparotomy is the procedure of choice. Surgical findings should be confirmed by histopathological study and individualized treatment should be offered. Intestinal intussusception is a rare surgical emergency in adults; malignant etiology should be suspected from the patient's clinical history.